Climate change and its effect on conservation and use of plant genetic resources for food and agriculture and associated biodiversity for food security - Jarvis, Andy; Upadhyaya, Hari D.; Gowda, C.L.L.; Aggarwal, Pramod K.; Fujisaka, S.; Anderson, B. (Food and Agriculture Organization of the United Nations, 2010)
We review the impacts and implications of climate change for the management and use of plant genetic resources for food and agriculture and associated biodiversity (PGRFA-AB). Climate change is predicted to bring about increased temperatures across the world in the range of 1.6°C to as much as 6°C by 2050. Although rainfall is predicted to increase globally, some areas will receive less annual rainfall, while others may receive much more. The timing of rains and crop growing periods will also change. The frequency and duration of extreme weather events are also predicted to increase, although uncertainty exists about the expected degree of changes. These predicted changes in climate are expected to have fairly widespread impacts on agriculture, with poor countries in the south highlighted as being particularly vulnerable, having already weak economies and limited institutional capacities to adapt. More specifically to PGRFA-AB, evidence suggests important risks to wild biodiversity, including crop wild relatives. Changes in climate are also likely to place new pressures on conservation of landraces of crop species.